2017
DOI: 10.7326/m17-0509
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Intravenous Immunoglobulin Treatment for Long-Standing Complex Regional Pain Syndrome

Abstract: Medical Research Council/National Institute for Health Research Efficacy and Mechanism Evaluation Program, Pain Relief Foundation, and Biotest United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Antinuclear antibodies are found in a disproportionately large fraction of patients with CRPS [ 51 ]. Additional data exist showing that a subset of patients treated with weekly plasmapheresis to lower autoantibody levels experienced prolonged symptom improvement, although a recent large randomized trial with low-dose intravenous immunoglobulin (IVIG) was ineffective [ 52 – 54 ]. Studies using sera and purified IgG preparations from CRPS patients have identified sympathetic neurons, muscarinic receptors, and alpha-1 adrenergic receptors as targets of these autoantibodies [ 6 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antinuclear antibodies are found in a disproportionately large fraction of patients with CRPS [ 51 ]. Additional data exist showing that a subset of patients treated with weekly plasmapheresis to lower autoantibody levels experienced prolonged symptom improvement, although a recent large randomized trial with low-dose intravenous immunoglobulin (IVIG) was ineffective [ 52 – 54 ]. Studies using sera and purified IgG preparations from CRPS patients have identified sympathetic neurons, muscarinic receptors, and alpha-1 adrenergic receptors as targets of these autoantibodies [ 6 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While CRPS has been long thought to arise as a result of an inflammatory process, more current work has it to be deemed an autoimmune condition. 1 3 , 5 12 Several observations lend strong support to this assertion. (i) The passive transfer of serum immunoglobulin G (IgG) antibodies from a CRPS patient, but not a normal patient, elicits CRPS-like pathology in mice.…”
Section: Crps As An Autoantibody-mediated Syndromementioning
confidence: 83%
“… 9 , 10 Against this assertion serves the evidence from the multicenter randomized blinded placebo-controlled trial that 0.5 g/kg intravenous immunoglobulin immunotherapy produced no benefit in CRPS compared with placebo-treated patients. 8 …”
Section: Crps As An Autoantibody-mediated Syndromementioning
confidence: 99%
“…Ultimately, this PPI exercise would have accepted an even higher number of patients treated for each responder; however, patients were content to negotiate these numbers acknowledging real‐world information on health economics (in the absence of predictive factors, the intervention may become unaffordable to a public healthcare system such as the UK National Health Service if the number of responders is low) and burden (repeat‐cannulation of a large number of patients for a rare positive response). Notably, recent research results indicate that although treatment‐refractory persistent CRPS is rare (estimated <1:2000/population) delivery of trials with up to 200 participants is feasible …”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent research results indicate that although treatment-refractory persistent CRPS is rare (estimated <1:2000/population) delivery of trials with up to 200 participants is feasible. 19,20 As the duration of pain relief following TPE would be an important outcome in a RCT, thus requiring long trial durations, and, equally, as data about any incremental treatment effect from repeat treatment would be advantageous, patients considered that a 12-months duration of such a trial would be acceptable provided that, as planned, all participants would be offered optional swop to the other treatment arm at the end of that time.…”
Section: Discussionmentioning
confidence: 99%